Unmasking the complexities of healthcare access in low-resource settings: a health systems approach to obstetric and under-5 healthcare in rural settings of Eastern Uganda - Rornald Muhumuza Kananura (Global Health Action)
Background Access to appropriate obstetric and under-5 healthcare services in low-resource settings is a challenge in countries with high mortality rates. However, the interplay of multiple factors within an ecological system affects the effectiveness of the health system in reaching those in need. Objective This study examined how multiple factors concurrently affect access to obstetric and child healthcare services in resource-poor settings Methods The research used social autopsies [in-depth interview] with mothers who experienced newborn death [n = 29], focus group discussions [n = 8] with mothers [n = 32], and fathers [n = 28] of children aged 6–59 months, and the author’s field observations in Eastern Uganda’s rural settings. The research employed narrative and inductive thematic analysis, guided by concepts of social interactions, behaviour, and health institutional systems drawn from system theory. Results The study unmasked multiple concurrent barriers to healthcare access at distinct levels. Within families, the influence of mothers-in-law and gender dynamics constrains women’s healthcare-seeking autonomy and agency. At the community level, poor transport system, characterised by long distances and challenging road conditions, consistently impede healthcare access. At the facility level, attitudes, responsiveness, and service delivery of health workers critically affect healthcare access. Negative experiences at health facilities profoundly discourage the community from seeking future health services. Conclusion The findings emphasise the persistent influence of structural and social factors that, although well documented, are often overlooked and continue to limit women’s agency and autonomy in healthcare access. Enhancing universal access to appropriate healthcare services requires comprehensive health systems interventions that concurrently address the healthcare access barriers.